Didactics of small languages: Hebrew at the Faculty of Arts, Palacky University in Olomouc - Ulicna, Lenka; Budikova, Hana; Tylcerova, Bara (e-Pedagogium, 2023)
This article deals with the teaching of modern Hebrew and is the result of the project IGA_FF_2022_033 Towards the didactics of small languages: Hebrew at the Faculty of Arts of the University of Olomouc. The authors draw attention to the difficulties associated with the teaching of small and exotic languages at universities, especially the lack of didactic training and methodological support for teachers of these languages.
Keywords: language didactics; tertiary education; modern Hebrew; small languages; exotic languages